2022
DOI: 10.1140/epjp/s13360-022-03314-1
|View full text |Cite
|
Sign up to set email alerts
|

The external photoevaporation of planet-forming discs

Abstract: Planet-forming disc evolution is not independent of the star formation and feedback process in giant molecular clouds. In particular, OB stars emit UV radiation that heats and disperses discs in a process called ‘external photoevaporation’. This process is understood to be the dominant environmental influence acting on planet-forming discs in typical star-forming regions. Our best studied discs are nearby, in sparse stellar groups where external photoevaporation is less effective. However, the majority of disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 354 publications
(510 reference statements)
0
16
0
Order By: Relevance
“…This leaves an additional mechanism for mass removal by external photoevaporation (e.g. Matsuyama et al 2003;Winter & Haworth 2022). This is supported by observational findings that discs near massive stars have lower masses than others (Ansdell et al 2017;van Terwisga et al 2020) and that clusters with a low ambient radiation field have longer disc lifetimes (Michel et al 2021).…”
Section: Introductionmentioning
confidence: 66%
“…This leaves an additional mechanism for mass removal by external photoevaporation (e.g. Matsuyama et al 2003;Winter & Haworth 2022). This is supported by observational findings that discs near massive stars have lower masses than others (Ansdell et al 2017;van Terwisga et al 2020) and that clusters with a low ambient radiation field have longer disc lifetimes (Michel et al 2021).…”
Section: Introductionmentioning
confidence: 66%
“…While the environments studied here are much less extreme than e.g. the ONC, A0 and B-type stars for the are much more common, and similar radiation fields are encountered by a large fraction of young stars even in the Solar neighborhood (Winter & Haworth 2022). This emphasizes the need for planet population syntheses to take this process into account, as well as resolved studies of the disks in these radiation environments, in order to link the observed exoplanet population to the well-studied nearby protoplanetary disks.…”
Section: Discussionmentioning
confidence: 93%
“…As such, these regions do not represent the more massive, clustered environments in which most stars form (Lada & Lada 2003;Bressert et al 2010). The median star in the galaxy is formed in a region with a higher surface density of young stars, and -as a result of the stellar mass distribution -will be within a few pc of an O-or B-type young star at some point in its early life (Winter & Haworth 2022). These young, massive stars affect the survival of disks in nearby stars through photo-evaporation, as shown by the presence of proplyds (O'Dell et al 1993) and by theoretical work (e.g., Scally & Clarke 2001;Haworth et al 2018;Concha-Ramírez et al 2019;Emsenhuber et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This results in terrestrial planets being able to survive in the former (although icy planets migrated to within 1 ) while they no longer exist in the latter. The link to the environment comes from the anticorrelation of disc lifetimes with external photoevaporation rate [ 163 ]. Absent this, disc lifetimes are correlated with their initial mass.…”
Section: Resultsmentioning
confidence: 99%